Aesthetic rhinoplasty: a paradigm shift towards cosmesis in Indian population - Agarwal, Shubham; Gupta, Nishant; Kataria, Tanmaya; Soni, Samanvaya; Jangid, Divya; Sharma, Man P.; Singhal, Pawan; Sharma, Anjani K.; Jat, Kailash S.; Nirwan, Siddharth (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: The tremendous growth of cosmetic surgery among Asians is largely due to strength of indigenous economies accompanying globalization. This increase in number can also be attributed to usage of social media as well as increased desire to look perfect. The current study is an attempt to measures aesthetic outcome and identify possible interactions between other possible outcome determinants. Methods: The present study was a 1.5 years prospective interventional study conducted at SMS Medical College, India from January 2021 to July 2022. A total of 51 samples were included in our study. The rhinoplasty outcome evaluation (ROE) questionnaire was used to assess patient satisfaction which was presented and completed by all patients before and after 6 months of surgery and data was analysed. Results: In the present study mean age of study participants was 25.7 years and most subjects (64.7%) were male and (35.3%) were female. Mean total ROE at pre-op and post-op 6 months was 35.05±13.4 and 57.4±27.9 respectively and mean Total ROE difference between pre-op and post-op 6 month was -22.4±36.1. This difference was found to be statistically significant (p value 0.0001). Conclusions: Aesthetic rhinoplasty in India is emerging as a lifestyle choice because of increased users of social media as well as awareness about procedures available for enhancing facial features. Our study gives a glimpse towards the shift of rhinoplasty in India and explains the possible reasons behind this shift.